COMPARATIVE ANALYSIS OF MOTIVATION AND WORK ETHIC OF OVERSEAS TRADERS AND LOCAL TRADERS - muhsyafii; SARNI (Prodi. Hukum Ekonomi Syariah, Fakultas Syariah, IAI Hamzanwadi Pancor Lombok Timur, 2024)
Motivation is a factor that can encourage individuals to carry out a certain activity. Meanwhile, Work Ethic emphasizes that creative work is a source of happiness and achievement. Hard work is considered a virtue so that a trader who does his work with hard work and high enthusiasm has a high chance of progressing in life, conversely if a person does not work hard to complete his work there is a big possibility that his life will fail. The conclusions from this research are as follows: 1.) The main motivation of overseas traders and local traders in working is to meet the needs of themselves and their families. Apart from family motives, the motivation of overseas and local traders in running their business is to increase the level of family welfare and raise the standard of living. This can be seen from the way it responds to the high and low levels of the number of consumers who choose to shop at its stalls and the level of income they earn. 2.) A good work ethic among fellow traders can have a positive influence on a healthy work environment so that business competition between traders is not too obvious. In relation to the work ethic between local traders and overseas traders in Pancor Village, a good work ethic can provide comfort so that it can influence productivity levels.